Synthesis, characterization, and the effects of organo-grafted nanoparticles in nickel coatings for enhanced corrosion protection. (December 2020) - Ngo, Ngan K.; Shao, Shuai; Conrad, Heidi; Sanders, Stephen F.; D'Souza, Francis; Golden, Teresa D.
Highlights: Metal-organo-ceramic nanocomposites were prepared as corrosion protection coatings. Diazonium synthesis procedure was used to graft ferrocene onto ceramic nanoparticles. Grafted nanoparticles were incorporated into a nickel film using electrodeposition. Hydrophobicity of the coating is increased by grafting with the organic moiety. Corrosion testing shows a 100 % improvement in corrosion protection for the coatings. Abstract: Metal-organo-ceramic nanocomposite coatings were prepared via electrodeposition as corrosion protection coatings. A diazonium synthesis procedure was used to successfully graft ferrocene onto CeO2 nanoparticles. The modified nanoparticles were characterized by fourier-transform infrared spectroscopy (FTIR), solid-state NMR, electrochemical techniques, atomic absorption spectroscopy (AAS), and thermogravimetric analysis (TGA). A mixture of the grafted nanoparticles and nickel ions was added to an electrolyte plating solution for deposition of a Ni Fc-CeO2 nanocomposite coating onto steel substrate as a corrosion protection layer. The effect of CeO2 and ferrocene-CeO2 nanoparticles on the formation, morphology, composition, and corrosion resistance of the nickel coating was investigated by potentiodynamic polarization, powder x-ray diffraction (XRD), scanning electrochemical microscopy (SEM), inductively coupled plasma mass spectrometry (ICP-MS), and electrochemical impedance spectroscopy (EIS).